Non-thermal techniques and the "hurdle" approach: How is food technology evolving?. (February 2023) - Bigi, Francesco; Maurizzi, Enrico; Quartieri, Andrea; De Leo, Riccardo; Gullo, Maria; Pulvirenti, Andrea
Abstract: Background: Food technology has played a crucial role since the beginning of human civilization. Throughout the centuries, the evolution of food processing has led to an increase of food safety and quality, enhancing the overall quality of human life. Lately, academic research and industries have gained awareness about the impact of conventional preservation technologies like heat sterilization and chemical preservatives on environment and economy, besides the detrimental effects on the organoleptic and nutritional quality of foods. This consciousness oriented the efforts towards more sustainable techniques, paving the way to a new "green era" of food technology. Scope and approach: This work explores seven non-thermal technologies, describing their theoretical principles, mechanism of action, effect on microorganisms, advantages, and limitations. Besides, the concept of hurdle technology to overcome the criticisms related to single processing techniques is highlighted. Key findings and conclusions: Non-thermal technologies have the potential to substitute conventional techniques for microbial inactivation, improving the safety and quality of food. The efficiency of each technique strongly relies on the process parameters (treatment intensity; exposure time), equipment (geometry; conformation), product (physical state; composition; viscosity; geometry), and microorganism characteristics (strain; concentration; growth phase; resistance mechanisms). In this sense, the hurdle approach allows to overcome the limitations related to the single technologies, broadening their efficiency and application range, and minimizing their impact on food quality. Further studies are recommended to better understand the mechanisms of mutual interaction among these techniques when combined together in specific conditions, in view of their scaling-up for commercial applications. Graphical abstract: Image 1 Highlights: Non-thermal techniques can substitute thermal treatments and chemical preservatives. The hurdle approach overcomes the limitations related to the single technologies. Hurdle technology broadens the efficacy and application range of single techniques. Hurdle technology minimises the impact on food quality.